Usage of a German prevention and health promotion web portal and cost per pageview: a life-cycle assessment - Kohler, Stefan; Keil, Thomas; Reinhold, Thomas; Müller-Riemenschneider, Falk; Willich, Stefan N.; Roll, Stephanie (Digital health, 2019)
Background Web portals providing health information online have the potential to reach large numbers of people. Yet few studies have assessed usage and costs of health portals, especially over an extended period of time.Objectives First, to assess the usage of a web portal on prevention and health promotion that was initiated by the German states of Berlin and Brandenburg. Second, to estimate average cost per pageview over the full web portal life-cycle.Methods Usage data were gathered through Google Analytics. The main usage metric assessed was pageviews originating from an IP address in Berlin or Brandenburg. Project cost data were reported by the local government and from own records. Descriptive and regression analyses were used to determine time trends in pageviews.Results The redesigned web portal Praeventionsatlas.de launched August 2011 and was discontinued March 2018. Analyzing the full calendar years only, the annual pageview number increased from 2012 (8492) to its peak in 2014 (11,876) and steadily decreased to its minimum in 2017 (7232). Pages of the web portal were most often viewed around lunchtime (12 to 1 p.m.), in the middle of the week (Wed to Thu), and at the beginning of the year (Jan to Feb). Adjusting for year, month, and weekday, the number of daily pageviews dropped on major public holidays (Easter ?9, Pentecost ?12, Christmas ?12 and New Year?s Eve and Day ?20; p?
Gesehen am 26.03.2025